Acceptability of rubber dam placement by pediatric patients treated for pulpotymy in U.P. College of Dentistry, 2nd Semester, 2011-2012 - Cas Daisy Jane V.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.